The reduction of the main engine’s power for a 15000 tdw chemical tanker regarding the achievement of EEXI and its influence on manoeuverability - Iulia Andreea Paun; Radu Bosoancă (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding)
EEXI was established as a measure for assessing the energy efficiency of existing vessels and aims to reduce CO2 in order to achieve IMO regulations. The purpose of this study is to calculate the EEXI for a 15000 twd chemical tanker and further evaluate the impact of this change on ship manoeuvrability. EEXI estimations were conducted using different approaches while manoeuvrability performances were evaluated by means of different simulation programs. The purpose of this study revolves around striking a balance between optimal operation and achieving energy efficiency.